The Effect of Using Interactive Simulation in Science Laboratory on Knowledge Levels of Science Laws and Computational Thinking Skills - Nurhan Atalay; Mehmet Mutlu (Mimbar Sekolah Dasar, 2023)
Today, teaching strategies and methods changing with technology require a radical transformation in the teaching of science laws, which form the basis of science subjects. In this study, computational thinking skills, which will allow students to use information and communication technologies in today's conditions and the effect of these skills on their knowledge levels about science laws were examined. A university in the Central Anatolian Region of Turkey served as the institution that provided the study sample, which consisted of 61 science preservice teachers who were enrolled in the university's Science Teaching Department. In this study, pretest-posttest control group design, one of the experimental designs, was used. The participants were randomly assigned to either the experimental group or the control group, with 30 people assigned to the experimental group and 31 participants assigned to the control group. To collect data, an achievement test with 20 questions aiming to measure the success levels of science laws by the researchers and the "Computerized Thinking Scale" for university students was used. At the end of the research process, it was concluded that the achievements of the students in the experimental group were significantly different from the students in the control group, and there was a significant difference in favor of the experimental group in all sub-dimensions of computational thinking and computational thinking.